ANTIBACTERIAL AND ANTIFUNGAL ACTIVITIES OF THE EXTRACT AND FRACTIONS OF AERIAL PARTS OF HELIOTROPIUM BACCIFERUM - Ullah, Riaz; Ahmad, Sohail; bibi, Ihteram; AbdEl-SalaSalam, Naser M.; Hussain, Hidayat; Ishaq, Muhammad Saqib; Adnan, Muhammad; Tariq, Akash; Ullah, Riaz (African Journal of Traditional, Complementary and Alternative Medicines, 2015)
Background: H. bacciferum belonging to the family Boraginaceae is an important medicinal plant. The current research was carried out to investigate the medicinal properties of this plant. Methodology: The crude (methanol fraction) and n-hexane, ethyl acetate, butanol and aqueous fractions were subjected to antibacterial and antifungal activities by using standard methodology available in literature. Bacterial strains of Salmonella typhi, Escherichia coli, Pseudomonas Aeroginosa, Staphylococcus aureus, Erwinia carotovora, Klebsiella Pneumoniae, Bacillus subtilis and Bacillus atrophaeus were used for antibacterial activity. Results: All the fractions were active against different bacterial strains but n-hexane and ethyl acetate showed (Zone of inhibition ranged from 18-30 mm) highest activity. The fungal strains, Trichoderma longibrachiantum, Aspergillus flavus, Aspergillus niger, Fusarium solani and Candida albican were used for antifungal activity. Excellent inhibitory effect was observed against all fungal strains. The minimum inhibitory concentration (MIC) against various fungal strains was determined. The minimum inhibitory concentrations (MICs) of the investigated plant fractions ranged from 0.5-2.00 mg/ml. Conclusion: The plant showed significant antibacterial and antifungal activities. All tested plant extracts exhibit activities against different fungal strains. The result against various microorganisms shows the therapeutic potential of the plant H. bacciferum